2016
DOI: 10.1097/md.0000000000005756
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation versus surgical resection for HCC meeting the Milan criteria

Abstract: The optimal treatment (liver transplantation [LT] vs surgical resection [SR]) for early-stage hepatocellular carcinoma (HCC) remains controversial.A total of 209 SR patients and 129 LT patients were identified at our institution. After eliminating 27 patients with Child–Pugh C, the data from 209 SR patients and 102 LT patients were analyzed using a propensity score matching (PSM) model. Forty-six pairs were generated. A subgroup analysis was conducted based on the alpha-fetoprotein (AFP) level or platelet coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
(51 reference statements)
0
17
0
1
Order By: Relevance
“…The reasons why the patients who met the Milan criteria did not receive LT in this study were: (1) refusal to LT; (2) failure of affording the high cost of LT; (3) organ shortage; (4) concern about severe adverse effects of long term oral immunosuppressive agents after LT. In addition, previous studies indicated that overall survival of patients with Milan criteria after liver resection (LR) were comparable to those after LT (12)(13)(14). This observation may be attributable to advances in liver surgery, perioperative therapies for patients with liver cirrhosis, and the development of advanced multimodality for the recurrent lesions.…”
Section: Patientsmentioning
confidence: 99%
“…The reasons why the patients who met the Milan criteria did not receive LT in this study were: (1) refusal to LT; (2) failure of affording the high cost of LT; (3) organ shortage; (4) concern about severe adverse effects of long term oral immunosuppressive agents after LT. In addition, previous studies indicated that overall survival of patients with Milan criteria after liver resection (LR) were comparable to those after LT (12)(13)(14). This observation may be attributable to advances in liver surgery, perioperative therapies for patients with liver cirrhosis, and the development of advanced multimodality for the recurrent lesions.…”
Section: Patientsmentioning
confidence: 99%
“…However, the prognosis of patients with HCC remains poor, probably due to diagnosis at a late stage. Other treatments include radiofrequency ablation (RFA), microwave ablation, high intensity focused ultrasound ablation, transarterial chemoembolization (TACE), and liver transplantation …”
Section: Introductionmentioning
confidence: 99%
“…Other treatments include radiofrequency ablation (RFA), microwave ablation, high intensity focused ultrasound ablation, transarterial chemoembolization (TACE), and liver transplantation. 6,7 Since the first laparoscopic liver hepatectomy (LH) in 1992, 8 and the report of the first LH for HCC was published in 1995, 9 laparoscopic hepatectomy is being increasingly used for HCC. Laparoscopic hepatectomy was initially considered controversial, but there has been constant improvement in laparoscopic techniques and devices, and accumulating data, which have led to a more widespread acceptance of LH as a minimally invasive approach for the resection of HCC over the last 15 years.…”
Section: Introductionmentioning
confidence: 99%
“…No prospective randomized studies has been conducted to compare the effectiveness of LR and LT in this type of patients. Though several retrospective studies focused on this issue, their results were controversial due to different eligibility criteria, especially in tumor size, lesion number and vascular invasion [ 9 11 , 13 , 14 ]. According to a meta-analysis comparing outcomes of LR and LT in patients with early HCC, LT group had a survival advantage in certain settings.…”
Section: Discussionmentioning
confidence: 99%